Big Data Analytics and Sustainable Supply Chain Management Practices among Manufacturing Enterprises in North-West Nigeria: A Mediating Role of Inventory Management - Olusegun, Kazeem Lekan; Nuraini, Hashimu Salaudeen; Akosile, Oluwafemi Ibraheem (Electronic Journal of Business and Management, 2026)
The growing need for harmonised approaches to enhance operational efficiency, minimise costs, and optimise delivery and distribution in today’s expanding, sporadic global supply chains and highly turbulent business environment has brought Big Data Analytics (BDA) to the forefront of managerial and scholarly attention. Consequently, an avalanche of literature has documented the positive influence of BDA on Sustainable Supply Chain Management Practices (SSCMP). However, despite this growing body of evidence, there remains a remarkable scarcity of studies that examine Inventory Management (IM) as a mediating mechanism between BDA and SSCMP among manufacturing enterprises. This study therefore investigated the mediating effect of IM on the relationship between BDA and SSCMP in order to extend prior findings. PLS-SEM was employed to test whether IM significantly mediates the relationship between BDA and SSCMP, using survey data obtained from 304 business owners and managers in the manufacturing sector in North-West Nigeria. The findings reveal that the effect of BDA on SSCMP is significantly mediated by IM. On the strength of this evidence, the study concludes that IM exerts a significant and positive mediating effect on the relationship between BDA and SSCMP. It therefore recommends that CEO as well as top managers of manufacturing enterprises should leverage BDA so as to analyse supply chain disruptions, identify potential risks, develop mitigation strategies, and equally deploy predictive analytics in order to optimise inventory allocation.